Analysis Of Factors Affecting Employee Performance - Ariyani Tista; Wulan Candra; Dewanti Navita; Efendi Bahtiar (SHS Web of Conferences)
This study analyzes the effect of Work Life Balance (WLB), Employee Retention, Employee Engagement, and Flexible Working Arrangements (FWA) on Employee Performance at CV. Abong IPA. In the era of globalization, employee performance is an important factor for organizational success. The study used a quantitative approach with data collection through questionnaires distributed to 35 employees. The results show that WLB, Employee Retention, and Employee Engagement have a significant influence on Employee Performance, while FWA does not. Simultaneously, the four variables have a strong influence, with a coefficient of determination (R²) of 81.6%. This study recommends companies to pay attention to work-life balance, retention, and employee engagement. Policies that support WLB and efforts to improve engagement and retention can improve employee performance. Although FWA is not significant, this aspect still needs to be considered to improve employee well-being.